2020
DOI: 10.3390/medicina56060270
|View full text |Cite
|
Sign up to set email alerts
|

Non-Steroidal Anti-Inflammatory Drug Etoricoxib Facilitates the Application of Individualized Exercise Programs in Patients with Ankylosing Spondylitis

Abstract: Background and objectives: The main objective of this study is to highlight the efficiency of different therapeutic means in patients with ankylosing spondylitis, resulting in the improvement of their quality of life. Materials and Methods: We conducted a randomized, longitudinal, controlled trial on 92 patients with ankylosing spondylitis over a period of 6 years. Disease activity was assessed using the BASDAI (Bath Ankylosing Spondylitis Disease Activity Index) score. The assessment of functional disabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Moreover, BASDAI is a subjective method of determining disease activity, the ASDAS score being a more reliable tool in assessing disease activity. In fact, not all tests used to quantify enthesitis measure the same characteristics; thus, there is a discrepancy between the scores of overall clinical activity and the disease activity at the entheseal level [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BASDAI is a subjective method of determining disease activity, the ASDAS score being a more reliable tool in assessing disease activity. In fact, not all tests used to quantify enthesitis measure the same characteristics; thus, there is a discrepancy between the scores of overall clinical activity and the disease activity at the entheseal level [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…81 Eight studies on NSAIDs were included, of which two non-inferiority RCTs in r-axSpA, one at low and one at unclear RoB (Table 2). [82][83][84][85][86][87][88][89] The first study demonstrated non-inferiority of two doses of etoricoxib (60 and 90 mg daily) versus naproxen 1000 mg daily on VAS spinal pain (SMD between etoricoxib 60 mg and 90 mg with naproxen: 0.07 (−0.24, 0.10) and 0.03 (−0.19, 0.26). 82 The second RCT demonstrated the non-inferiority of two doses of celecoxib (400 mg and 200 mg) versus diclofenac 150 mg daily in VAS global pain (SMD not possible to calculate).…”
Section: Efficacy Of Pharmacological Interventions: Non Tsdmardsmentioning
confidence: 99%